Disseminating International Human Rights Instruments: a Study of Legal Policies that Violates Women’s Human Rights - Sagala, R. Valentina (Yayasan Jurnal Perempuan, 2015)
This paper paper examines human rights including women’s human rights (women’s rights), the adoption of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), and other international human rights instruments. Referring to CEDAW’s principles together with human rights principles, States are urged to create law that promotes women’s perspective. Unfortunately until now, there are many policies and laws, at any levels— national and province/district/city—discriminate against women. Regarding this, this paper will focus to list on Bills which become the advocacy priority for women’s movement in Indonesia.